2016
DOI: 10.4018/ijsse.2016010103
|View full text |Cite
|
Sign up to set email alerts
|

Steps Towards Fuzz Testing in Agile Test Automation

Abstract: Including and automating secure software development activities into agile development processes is challenging. Fuzz testing is a practical method for finding vulnerabilities in software, but has some characteristics that do not directly map to existing processes. The main challenge is that fuzzing needs to continue to show value while requiring minimal effort. The authors present experiences and practical ways to utilize fuzzing in software development, and generic ways for developers to keep security in min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…While there exists a series of suggested methods how to conduct security engineering activities in an agile project (see e.g. Alnatheer, Gravel & Argles, 2010;Baca & Carlsson, 2011;Beznosov & Kruchten, 2004;Fitzgerald, Stol & Sullivan, 2013;Ge, Paige, Polack & Brooke, 2007;Pietikäinen & Röning, 2014;, the empiric evidence is still largely anecdotal and the cases reported specific to an industry or a single company. The study reported in this paper is exploratory, and thus the research, by its nature, explorative.…”
Section: Introductionmentioning
confidence: 99%
“…While there exists a series of suggested methods how to conduct security engineering activities in an agile project (see e.g. Alnatheer, Gravel & Argles, 2010;Baca & Carlsson, 2011;Beznosov & Kruchten, 2004;Fitzgerald, Stol & Sullivan, 2013;Ge, Paige, Polack & Brooke, 2007;Pietikäinen & Röning, 2014;, the empiric evidence is still largely anecdotal and the cases reported specific to an industry or a single company. The study reported in this paper is exploratory, and thus the research, by its nature, explorative.…”
Section: Introductionmentioning
confidence: 99%
“…A fuzz approach to security testing was presented by Pietikäinen et al The authors emphasised the challenges, experiences, and practical ways of utilizing fuzzing in soft-ware development, focussing on software security aspects [6].…”
Section: Introductionmentioning
confidence: 99%